Dynamics of Banking Profitability in Asia: A Comparative Study of ROA, ROE, and NIM in Southeast Asian and South Asian Banks, 2016–2025 - Winanda Wahana Warga Dalam (Politeknik Negeri Batam, 2026)
This study examines whether bank performance differs between Southeast Asia and South Asia during 2016–2025. Using a quantitative comparative design, the study analyzes 172 banks consisting of 78 Southeast Asian banks and 94 South Asian banks after outlier treatment. Bank performance is measured using return on assets (ROA), return on equity (ROE), and net interest margin (NIM), while non-performing loans, Tier 1 ratio, loan-to-deposit ratio, cost-to-income ratio, and bank size are used as explanatory control variables. Independent-samples t-tests show that ROA and NIM do not differ significantly between the two regions, whereas ROE differs significantly, with South Asian banks reporting higher average ROE. The findings indicate that regional performance differences are more visible in shareholder return than in asset productivity or interest intermediation. The study contributes to comparative banking literature by showing that bank performance across regions is multidimensional and must be interpreted alongside risk, capital, and institutional context.